Emergency Chest Pain Center - Marwa A. Sabe, MD, MPH; Frank J. Kaeberlein, MD; Sharif A. Sabe, MD, MA; Allyson Kelly, BSN, MBA; Tracy Summerfield; Ahmed A. Sabe, MD (JACC: Advances)
Background: Percutaneous coronary intervention is the preferred treatment for acute ST-segment elevation myocardial infarction (STEMI), and shorter door-to-balloon time (D2B) is associated with lower mortality. We implemented a catheterization laboratory within the emergency department (ED) as a novel strategy to reduce D2B. Objectives: The purpose of this paper was to compare D2B and mortality in STEMI patients presenting to ED vs standard catheterization labs at a community hospital. Methods: We prospectively reviewed consecutive patients presenting with STEMI to our institution between 1998 and 2011 and treated with primary percutaneous coronary intervention. The primary endpoints were D2B and time to death. A multivariable linear regression model was used to assess the relationship between catheterization lab location and D2B. The relationship between D2B and mortality was examined using a Cox proportional hazards model. Results: We included 1,053 STEMI patients (553 in ED vs 500 in standard catheterization labs). Both groups had similar age, sex, race, diabetes, left main disease, and Killip class on presentation. Standard catheterization lab patients were more likely to have left ventricular ejection fraction <40% (11% vs 6.5%). D2B was shorter in ED vs standard cath lab patients (54 vs 83 minutes, P < 0.001). ED catheterization lab patients were more likely to have <30-minute D2B (17% vs <1%, P < 0.001). After covariate adjustment, ED catheterization lab patients had lower 30-day (adjusted hazard ratio [adj HR]: 0.54, 95% confidence interval [CI] 0.29-0.99), 1-year (adj HR: 0.58, 95% CI: 0.37-0.91), and 10-year mortality (adj HR: 0.39, 95% CI: 0.29-0.53) than standard catheterization lab patients. Conclusions: Implementation of an ED catheterization lab is a feasible strategy which may reduce D2B and STEMI mortality.